(untitled) (PHARMACON, 2013)
The aim of this research was to analyze mercury reduction power from patient urine with teeth amalgam which used for mercury detoxification. The research was descriptive which isolate 5 samples of patient urine from Bahu PUSKESMAS. Bacteria were grow in a media wich consist of 5, 10, 20, 40 and 60 ppm of HgCl2. Bacteria which grow in the highest concentration of mercury were identified and tested it reduction power against HgCl2. The result shows that there were 3 isolates which bacteria can grow with HgCl2 60 ppm namely Isolate U1.3, U3.1, and U3.3. Identification result found that isolate U1.3 and U3.1 were positive gram bacteria, rod, and motil, although U3.3 was negative gram bacteria, rod and not motil. Result of mercury reduction shows that in 24 hours, the three isolates reduce 100% mercury in nutrient broth, it concluded that isolates were highly resistant mecury bacteria. It can be used to detoxify mercury. Â Key words : mercury reduction, urine, PUSKESMAS